Guest Editorial Special Issue on the 2018 Workshop on the Algorithmic Foundations of Robotics (WAFR) - Tapia, Lydia; Morales, Marco; Hutchinson, Seth; Sanchez-Ante, Gildardo (IEEE transactions on automation science and engineering, 2021)
This Workshop on the Algorithmic Foundations of Robotics (WAFR) Special Issue of the IEEE Transactions on Automation Science and Engineering (T-ASE) brings together eight extended articles from the thirteenth WAFR. While these eight articles span several application domains, they demonstrate advances in automation through algorithmic development and analysis. Nomination to this Special Issue was done in coordination with the entire program committee and guest edited by the four WAFR Co-Chairs. The articles in this Special Issue highlight cutting-edge research in general tools for motion planning, learning, control, manipulation, sensor-based planning, and robotic design.